AN AN STUDY OF ANALGESIC ACTIVITY OF HAFFNER’S TAIL CLIP METHOD ON ALBINO WISTAR RATS OF SOME POLYHERBAL FORMULATION - LOKENDRA SINGH, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Herbal drugs are more beneficial better than aspirin because this is an herb so no side effect this drug and it is easy to collect or use to as herbal drugs. Words are inadequate to describe the motivation for my work given to my beloved guide. I would like to add special thanks to my guide Gauravbilwal, for their guidance, support, and encouragement. Purpose (Hypothesis): The main purpose of this article pays to attention for herbal drugs because they are naturally old effective drugs. As well as, Ayurveda treatment is very older effective technique. Design/Method: Haffner gave to this technique of determining analgesic are around in 1929. Procedure: This technique according to tail if clipped with any object and tightly or will be compression generation of pain in the tail as well as mice starting to bite that portion of its tail, and could evaluate and recorded the response how much it bites tail quickly or in potential. Using this simple yet important marvel, we may apply the drug to be evaluated and record the response whether it bites tail quickly or in potential. If given drugs have analgesic likely, then rat will not bite its tail so frequently. Mice that do not show any response within 15 s will reject from the experiment. Results: The found in analgesic activity of additional compounds test to significant on tail flick test than acetic acid-induced test and thus it appears that the test compounds inhibit predominantly the peripheral pain mechanism. The results of the study indicate that the extracts of polyherbal plants of analgesic activity by reducing the abdominal constriction significantly and may supposed to have a possible role in inhibition of cyclooxygenase in the prostaglandin pathways (p****<0.0001, ***0.0001, *0.05). Conclusion: The present study showed the significant analgesic effect of both aqueous and alcoholic at 400 mg/kg doses in albino rats, we reported for the 1st time analgesic effect of different plants (Curcuma longa, Colchicaceae, Colocynthis, Withania somnifera, and Achyranthes aspera) in Haffner’s tail clip models. Aspirin has each uncoated effervescent tablet content are acetylsalicylic acid I.P. 325 mg. Finally summarized in this article represent a most effective results of herbal drugs equalized allopathic drugs without any other side effect. Hence, this is very usefully combination of Ayurveda drugs.